2006
DOI: 10.1016/j.cmet.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

ATM-dependent suppression of stress signaling reduces vascular disease in metabolic syndrome

Abstract: Metabolic syndrome is associated with insulin resistance and atherosclerosis. Here, we show that deficiency of one or two alleles of ATM, the protein mutated in the cancer-prone disease ataxia telangiectasia, worsens features of the metabolic syndrome, increases insulin resistance, and accelerates atherosclerosis in apoE-/- mice. Transplantation with ATM-/- as compared to ATM+/+ bone marrow increased vascular disease. Jun N-terminal kinase (JNK) activity was increased in ATM-deficient cells. Treatment of ATM+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
224
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(235 citation statements)
references
References 59 publications
(65 reference statements)
10
224
1
Order By: Relevance
“…ATM, the gene mutated in the cancer-prone human disease ataxiatelangiectasia (AT), is a protein kinase that serves as a critical mediator of signaling pathways that facilitate the response of mammalian cells to ionizing radiation (IR) and other agents that induce DNA double-strand breaks (4). Recently, however, ataxiatelangiectasia mutated (ATM) has been implicated in metabolic pathways unrelated to DNA damage (5).…”
mentioning
confidence: 99%
“…ATM, the gene mutated in the cancer-prone human disease ataxiatelangiectasia (AT), is a protein kinase that serves as a critical mediator of signaling pathways that facilitate the response of mammalian cells to ionizing radiation (IR) and other agents that induce DNA double-strand breaks (4). Recently, however, ataxiatelangiectasia mutated (ATM) has been implicated in metabolic pathways unrelated to DNA damage (5).…”
mentioning
confidence: 99%
“…On the other hand, diets that are rich in antioxidant components may prevent oxidative DNA lesions and the development of senescent adipocytes, which may prevent the development of obesity and the metabolic syndrome in response to proinflammatory diets and environmental toxins. These findings, together with other DNA repair enzyme-defective mouse models (3,4,(6)(7)(8), suggest that reduction of genome integrity, regardless of whether it is induced by defective DNA repair or exogenous agents, contributes causatively to the development of the metabolic syndrome. Given that most people become overweight or moderately obese with age rather than severely obese (48), the mechanistic relationship between loss of genome integrity and development of the metabolic syndrome with age needs to be further studied.…”
Section: Impact Of Pol η On Cellular Senescence and Adipogenesis Usingmentioning
confidence: 94%
“…In addition, defective DNA repair enzymes are associated with the metabolic symptom; for example, DNA glycosylase (Neil1)-and OGG1-deficient mice are obese (3)(4)(5), and nucleotide excision repair protein ERCC1-XPF deficiency causes lipodystrophy (6). Furthermore, DNA damage response protein ataxia telangiectasia mutated (ATM) suppresses JNK activity through p53 signaling and mediates an antioxidant action that has been suggested to be relevant to the metabolic syndrome (7). Nucleotide excision repair XP-A protein may affect metabolism by altering mitochondrial function (8).…”
mentioning
confidence: 99%
“…Interestingly, recent studies suggested that human ATM regulates mTORC1 pathway either positively or negatively depending on the presence or absence of stresses 44,45,[50][51][52] . Given that TCTP makes a complex with ATM and functions in both nucleus and cytoplasm, it could be possible that TCTP and ATM might share a function for modulating mTORC1 pathway.…”
Section: Identification Of Datm As a Direct Binding Partner For Dtctpmentioning
confidence: 99%